2011
DOI: 10.5209/rev_sjop.2011.v14.n1.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Risk Propensity Using an Objective Instrument

Abstract: Risk propensity is the stable tendency to choose options with a lower probability of success, but greater rewards. Its evaluation has been approached from various perspectives: from self-report questionnaires to objective tests. Self-report questionnaires have often been criticized due to interference from voluntary and involuntary biases, in addition to their lack of predictive value. Objective tests, on the other hand, require resources that make them difficult to administer to large samples. This paper pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Risk assessment. Tolerance for risk is referred to as risk propensity, and it is defined as individuals' likelihood to select options that lead to the greatest rewards at the cost of lowered probabilities of success (Abad, Sanchez-Iglesias, & Tella, 2011). Research repeatedly has demonstrated that risk is a potent factor in determining whether individuals enact social influence behaviors (e.g., Morrison & Bies, 1991;Rudman, 1998;Shaughnessy, Treadway, Breland, Williams, & Brouer, 2011).…”
Section: Social Influence Opportunity Evaluationmentioning
confidence: 99%
“…Risk assessment. Tolerance for risk is referred to as risk propensity, and it is defined as individuals' likelihood to select options that lead to the greatest rewards at the cost of lowered probabilities of success (Abad, Sanchez-Iglesias, & Tella, 2011). Research repeatedly has demonstrated that risk is a potent factor in determining whether individuals enact social influence behaviors (e.g., Morrison & Bies, 1991;Rudman, 1998;Shaughnessy, Treadway, Breland, Williams, & Brouer, 2011).…”
Section: Social Influence Opportunity Evaluationmentioning
confidence: 99%